Pelatihan Daring Penulisan Proposal Tesis Mahasiswa Program Magister Program Pascasarjana - Areski Wahid; Muhammad Basri; Muhammad Arham; Amiruddin Tawe; St. Zulaiha Nurhajarurahmah (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2025)
This online training on writing thesis proposals is intended for students of Universitas Negeri Makassar, Postgraduate Masters Program to overcome academic challenges in preparing proposals, such as difficulties in formulating research problems, managing references, and meeting methodological standards. Through a structured online training method including needs analysis, distribution of interactive materials, scheduled training, formative evaluation, and individual mentoring, this activity succeeded in significantly improving participants' competencies. The results showed an increase in understanding of proposal components by 35% (average quiz score rose from 55 to 82), mastery of methodology (78% of participants were more confident), as well as increased motivation (45% to 78%) and successful submission of draft proposals (>70% approved with minor revisions). The flexibility of online learning and the scaffolding approach are key to its effectiveness, although technical challenges such as internet connectivity need to be anticipated. This training proves that technology integration in academic mentoring can be a strategic model for the quality of postgraduate research.